2022
DOI: 10.20983/decumanus.2022.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización desde la psicología ambiental de un ecosistema atípico en áreas verdes urbanas

Abstract: La investigación en psicología ambiental ha buscado las características que hacen que un escenario natural sea también un escenario salutogénico. Aunque se reconoce que las características naturales de los ambientes es lo que otorga la cualidad salutogénica, hay pocos estudios que especifican el hábitat usado como estímulo para provocar la respuesta salutogénica y, cuando lo hacen, recurren a categorías generales, como bioma. Las categorizaciones más específicas sobre un espacio natural y sus características s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…Kaplan and Kaplan (1989) suggested that openness is restorative when adding a landmark to the scene to facilitate orientation, while it loses restorativeness points if the environment seems uniform, indistinguishable; that is, the Open PSD could be modified in its restorative quality by adding or removing that reference point, but still perceived as Open. Likewise, it is suggested that the same PSD may have different expressions depending on the host ecosystem (Del Carmen-Robles et al, 2022). In this case, the TT in its wildest state (the Natural and Cohesive PSDs) seems to lose points in terms of restorativeness on account of the lower levels of perceived coherence and compatibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kaplan and Kaplan (1989) suggested that openness is restorative when adding a landmark to the scene to facilitate orientation, while it loses restorativeness points if the environment seems uniform, indistinguishable; that is, the Open PSD could be modified in its restorative quality by adding or removing that reference point, but still perceived as Open. Likewise, it is suggested that the same PSD may have different expressions depending on the host ecosystem (Del Carmen-Robles et al, 2022). In this case, the TT in its wildest state (the Natural and Cohesive PSDs) seems to lose points in terms of restorativeness on account of the lower levels of perceived coherence and compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Six variants were obtained, for the sole purpose of reducing the effects of order when viewing the stimuli, which were randomly applied to the participants. The stimuli evaluated consisted of 20 photographs taken from a previous study (Del Carmen-Robles et al, 2022). These images were evaluated by two groups of judges: (1) 10 experts in ecology, who confirmed the images as representative of the TT ecosystem; (2) 4 landscape professionals, who categorized the materials into one of the eight PSDs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations